2013
DOI: 10.1093/annonc/mds213
|View full text |Cite
|
Sign up to set email alerts
|

Ipilimumab in combination with paclitaxel and carboplatin as first-line therapy in extensive-disease-small-cell lung cancer: results from a randomized, double-blind, multicenter phase 2 trial

Abstract: These results suggest further investigation of ipilimumab in ED-SCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
383
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 560 publications
(395 citation statements)
references
References 43 publications
6
383
1
5
Order By: Relevance
“…However, no statistically significant differences were recorded. Interestingly, a subgroup analysis of this study found that the benefit of phased ipilimumab was more pronounced in patients with squamous cell lung cancer with HR for irPFS and OS of 0.55 (95% CI 0.27 --1.12) and 0.48 (95% CI 0.22 --1.03), respectively [19]. Consequently, this led to the initiation of a Phase III clinical trial evaluating the efficacy of phased ipilimumab in patients with squamous cell histology (NCT01285609) [20].…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 64%
See 1 more Smart Citation
“…However, no statistically significant differences were recorded. Interestingly, a subgroup analysis of this study found that the benefit of phased ipilimumab was more pronounced in patients with squamous cell lung cancer with HR for irPFS and OS of 0.55 (95% CI 0.27 --1.12) and 0.48 (95% CI 0.22 --1.03), respectively [19]. Consequently, this led to the initiation of a Phase III clinical trial evaluating the efficacy of phased ipilimumab in patients with squamous cell histology (NCT01285609) [20].…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 64%
“…Of note, grade 3 or 4 elevations in alanine aminotransferase were noted in phased and concurrent ipilimumab groups, but none in the control group. Overall, the rates of grade 3 --4 AEs were 21, 17 and 9% for the concurrent ipilimumab, phased ipilimumab and control groups, respectively [19].…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 95%
“…The mechanisms of action, the outcomes and the toxicity profiles of these drugs are discussed here. Most of these moAbs achieved significant improvement of overall survival by the combination with standard [113] NSCLC (No-Squ) [114] Ipilimumab Anti-CTLA-4 SCLC [107] NSCLC [108] Tremelimumab Anti-CTLA-4 Melanoma…”
Section: Resultsmentioning
confidence: 99%
“…No toxic death was registered [105]. A promising field of research on ipilimumab is represented by lung cancer [106,107]. Two Phase III trials have evaluated ipilimumab in both advanced NSCLC [108] and extensive-stage SCLC [109], showing very promising results.…”
Section: Anti-ctla-4 (Ipilimumab)mentioning
confidence: 99%
“…Phased ipilimumab, concurrent ipilimumab and control, respectively, were associated with median median PFS of 5.2, 3.9 and 5.2 months; median OS of 12.9, 9.1 and 9.9 months. Overall rates of grade 3/4 irAEs (immun-related advers events) were 17, 21 and 9% for phased ipilimumab, concurrent ipilimumab and control, respectively [14]. A phase 3 trial comparing the efficacy of ipilimumab plus etoposide/platinum versus etoposide/platinum in patients with newly diagnosed ED-SCLC (NCT01450761) is currently ongoing.…”
Section: Introductionmentioning
confidence: 99%